Associations between visual function and ultrastructure of the macula and optic disc after childhood cataract surgery. Issue 6 (16th November 2021) - Hansen, Mathias Møller; Bach Holm, Daniella; Kessel, Line
Abstract: Purpose: To investigate the association between visual function and ultrastructural characteristics of the retina and optic disc in children operated for cataract and factors influencing this relationship. Methods: We included 56 children aged 7–18 years who had been operated for bilateral or unilateral cataract. Three‐dimensional swept source OCT scans of the macula and the optic disc were obtained using the Triton OCT (Topcon, Corporation, Tokyo, Japan). Best corrected distance visual acuity was measured using the HOTV 3 Meter visual chart. Contrast vision was evaluated using the Freiburg Visual Acuity Contrast Test (FrACT). Healthy fellow eyes of the unilateral group were used as control eyes. Results: We did not find any associations between visual acuity or contrast sensitivity and structural retinal parameters. Shorter axial length, the presence of glaucoma and pseudophakia (opposed to aphakia) were all significant predictors of greater mean macular thickness in a multiple regression analysis, (p = 0.039). Two children had foveal hypoplasia, and one child had a right eye with a thin, disorganized retina. Conclusions: Children with pseudophakia have a thicker macula but this does not seem to be related to visual function. Obtaining high quality OCT scans of the macula and optic disc in severely visually impaired children with glaucoma and/or nystagmus is challenging. We found structural macular changes which contributed to poor vision but most eyes with very reduced vision were difficult to image, and the prevalence of structural changes may be underestimated.